Differences in the toxin profiles of Alexandrium ostenfeldii (Dinophyceae) strains isolated from different geographic origins: Evidence of paralytic toxin, spirolide, and gymnodimine. (1st September 2015) - Salgado, Pablo; Riobó, Pilar; Rodríguez, Francisco; Franco, José M.; Bravo, Isabel
Abstract: Among toxin-producing dinoflagellates of the genus Alexandrium, Alexandrium ostenfeldii is the only species able to produce paralytic shellfish poisoning (PSP) toxins, spirolides (SPXs) and gymnodimines (GYMs). In this study we characterized and compared three A. ostenfeldii strains isolated from the Baltic, Mediterranean, and southern Chile Seas with respect to their toxin profiles, morphology, and phylogeny. Toxin analyses by HPLC–FD and LC–HRMS revealed differences in the toxin profiles of the three strains. The PSP toxin profiles of the southern Chile and Baltic strains were largely the same and included gonyautoxin (GTX)-3, GTX-2, and saxitoxin (STX), although the total PSP toxin content of the Chilean strain (105.83 ± 72.15 pg cell −1 ) was much higher than that of the Baltic strain (4.04 ± 1.93 pg cell −1 ). However, the Baltic strain was the only strain that expressed detectable amounts of analogues of GYM-A and GYM-B/-C (48.27 ± 26.12 pg GYM-A equivalents cell −1 ). The only toxin expressed by the Mediterranean strain was 13-desmethyl SPX-C (13dMeC; 2.85 ± 4.76 pg cell −1 ). Phylogenetic analysis based on the LSU rRNA showed that the studied strains belonged to distinct molecular clades. The toxin profiles determined in this study provide further evidence of the taxonomic complexity of this species. Highlights: Chilean and Baltic strains showed the same PSP toxin profiles. PSP toxins of Chilean strain were much higher than Baltic strain. The Baltic strain produced also analogues of GYM-A and GYM-B/-C. Mediterranean strain only produced 13-desmethyl SPX-C.